General and special education inclusion in an age of change roles of professionals involved - Bakken, Jeffrey P.; Obiakor, Festus E. (Advances in special education ;, 2016)
This volume addresses general and special education inclusion and how the education field has changed over time. The topic of inclusion has transformed over the years from when it was first introduced and as a result of legislation, new trends, and current research investigations. In addition, this topic can be somewhat controversial depending on the disability the child might have or those professionals involved in the process of instructing individuals with disabilities. Currently, there is no comprehensive resource that effectively covers these advances with the breadth of topics as this volume. This volume will address the most current perspectives and issues related to general and special education inclusion and will be written by leaders in the field with particular expertise in this area. This volume will be an excellent resource for special educators, administrators, mental health clinicians, school counsellors, and psychologists. The layout of the volume will allow readers to follow general and special education inclusion in a very logical and thoughtful process from students with high incidence disabilities to those with low incidence disabilities.